2022
DOI: 10.1111/eea.13168
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting impacts of herbivore induction and elevated atmospheric CO2 on silicon defences and consequences for subsequent herbivores

Abstract: Plants are often sequentially attacked by multiple herbivores; feeding by one herbivore can alter host plant quality that affects the performance of subsequent herbivores. Previous studies suggest that silicon (Si) is a highly inducible defence in grasses (Poaceae) following herbivory, so could mediate such temporally separated insect herbivore interactions. Elevated atmospheric CO2 concentrations (eCO2), in contrast, often reduce Si accumulation, which potentially weakens this interaction. We examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The effects of CO 2 in this study on Si concentrations are broadly similar to the few studies exploring this, whereby elevated CO 2 leads to decreased Si accumulation (Ryalls et al, 2017;Biru et al, 2022;Johnson et al, 2022;Johnson et al, 2023), whereas reduced CO 2 leads to increased Si accumulation. To the best of our knowledge, the current study is only the third study to investigate the latter (Biru et al, 2020;Biru et al, 2021).…”
Section: Direct and Si-mediated Impacts Of Co 2 On The Activity Of An...supporting
confidence: 78%
See 1 more Smart Citation
“…The effects of CO 2 in this study on Si concentrations are broadly similar to the few studies exploring this, whereby elevated CO 2 leads to decreased Si accumulation (Ryalls et al, 2017;Biru et al, 2022;Johnson et al, 2022;Johnson et al, 2023), whereas reduced CO 2 leads to increased Si accumulation. To the best of our knowledge, the current study is only the third study to investigate the latter (Biru et al, 2020;Biru et al, 2021).…”
Section: Direct and Si-mediated Impacts Of Co 2 On The Activity Of An...supporting
confidence: 78%
“…Understanding the diminishing levels of Si-based plant defences against herbivores under future elevated atmospheric CO 2 concentrations has received limited attention. Previous studies have shown that elevated CO 2 concentrations decrease Si accumulation in different Poaceae genera (e.g., grass species and wheat) Biru et al, 2022;Johnson et al, 2022), and this was associated with reduced Si defences while increasing herbivore performance; however, this effect is not always reproducible (Frew et al, 2017). The impact of elevated CO 2 on Si defences reflects that plants switch from Si defences to Cbased defences due to higher C availability under this scenario Johnson et al, 2022).…”
Section: Diminishing Si Defence With Rising Comentioning
confidence: 91%
“…Moreover, Si is known to alter grass physical defences such as macrohairs, silica cells and prickle cells, which are linked to reduced feeding by insect herbivores (Hartley et al 2015, Biru et al 2021). Additionally, Si uptake and accumulation has been shown to be induced following herbivory (Massey et al 2007, Islam et al 2020, Biru et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The lower production of frass under reduced CO 2 , which we used 2 concentrations decrease Si accumulation in different Poaceae genera (e.g. grasses species and wheat)(Johnson and Hartley 2018, Biru et al 2022, Johnson et al 2022, and this was associated with reduced Si defences while increasing herbivore performance; however, this effect is not always reproducible(Frew et al 2017). The impact of elevated CO 2 on Si defences re ect that plants switch from Si defences to C-based defences due to higher C availability Hartley 2018, Johnson et al 2022).…”
mentioning
confidence: 99%
“…Plants are constantly under attack by above- and below-ground enemies such as viruses, bacteria, fungi, nematodes and insect herbivores (Stout et al 2006 ). The effects of these attackers can take place either simultaneously or sequentially, and in the latter case lead to plant-mediated indirect interactions where early-arriving attackers positively or negatively affect the performance of subsequent attackers (Wang et al 2014 ; Moreira et al 2015 ; Biru et al 2022 ). These plant‐mediated interactions are determined by the magnitude as well as type of plant responses which involve both mechanical (e.g.…”
Section: Introductionmentioning
confidence: 99%